Sustainable fresh strawberry consumption: environmental, genetically modified food, and climate concerns in Europe and North Africa - Zeneli, Fjona; Ventura, Vera; Frisio, Dario Gianfranco (Frontiers in Sustainable Food Systems, 2024)
Background and gap in the literature: Seasonal strawberries are a tasty fruit with plenty of significant health and environmental benefits. Despite these attributes, the determinants influencing strawberry consumption remain underexplored. Few, existing research are focused on conventional factors such as taste, freshness, and price, leaving aside some important, current dimensions such as consumers' environmental attitude, sustainability, Genetically Modified (GM) food knowledge, and climate change concerns. This article aims to explore the impact of the above-mentioned factors on the purchasing behavior of strawberries among consumers. Methodology: A designed questionnaire for a final sample of 2,378 consumers from Italy, Germany, France, Spain, Turkey, and Morocco was used to collect data about socio-demographic attributes, strawberry purchasing habits, respondents' level of knowledge on the topic of genetically modified food (GM) and climate change issue. The generalized ordinal logistic approach was performed deriving from the ordinal qualitative type of our two variables of interest (seasonal and non-seasonal strawberries purchase) and relaxing the assumption of parallel lines. Main results: From the socio-demographic factors, the more educated individuals, living in urban areas and having higher income levels are more likely to purchase frequently seasonal strawberries, while older people buy less frequently non-seasonal strawberries. Individuals who are more aware of sustainability issues, exhibit sustainable behaviors, and have more climate change concerns are more likely to buy less frequently nonseasonal strawberries, consisting of the most important result of our analysis. Implications: These results offer a comprehensive understanding of other drivers than the conventional ones related to seasonal and non-seasonal strawberry purchase patterns, giving important insights for policymakers in formulating tailored interventions for other dimensions: promoting sustainable agricultural practices (following the seasonality of the fruit), increasing consumer awareness about the environmental implications of the non-seasonal fruit purchases, and shifting individual eating patterns towards more sustainable and healthy ones (fresh and seasonal fruit consumption).